Evaluasi kesesuaian lahan untuk budidaya tebu berdasarkan sistem zonasi agroekologi di Jawa Timur, Indonesia - Purnamasari, Riska Ayu (Innovation Centre for Tropical Sciences, 2024)
Agroecological zoning system is essential to accelerate the production of plantation crops such as sugarcane. This is a tool that helps to identify the most suitable areas for growing specific crops based on the physical and biological characteristics of the land. The ideal conditions for sugarcane growth can be achieved from optimal planting land conditions and adequate climate and fertilization. Land use planning is key to the sustainability of plantation crops in Indonesia. In this study, we used land suitability evaluation for sugarcane cultivation using an agroecological zoning system. Multisource of suitability criteria was used from the thematic map that included the land use/land cover map, slope map, rainfall map, and soil type map as physical and biological characteristics of the land. On the land suitability map for sugarcane cultivation, the results are in the form of land area that was adjusted to the Food and Agriculture Organization indicators regarding land suitability class. We found that 23.20% of the area (11,149.49 km2) was very suitable for sugarcane cultivation, 30.18% (14,499.67 km2) was moderately suitable, 36.05% (17,321.71 km2) was marginally suitable, and 10.55% (5,068.25 km2) was not suitable for sugarcane plantation. In this study, it was found that around 1,114,949 ha of land in East Java had the potential to become sugarcane plantations based on the agroecological zoning system. This research recommended that the integrated approach of Geographic Information Systems (GIS) with satellite remote sensing vegetation datasets utilization might help to develop the site-specific management of sugarcane plantations. Keywords: agroecological zone, land suitability, mapping, remote sensing, sugarcane.